Life Sciences, Society and Policy - Zwart, Hub; Chadwick, Ruth
The purpose of Life Sciences, Society and Policy (LSSP) is to analyse social, ethical and legal dimensions of the most dynamic branches of life sciences and technologies, and to discuss ways to foster responsible innovation, sustainable development and user-driven social policies. LSSP provides an academic forum for engaged scholarship at the intersection of life sciences, philosophy, bioethics, science studies and policy research, and covers a broad area of inquiry both in emerging research areas such as genomics, bioinformatics, biophysics, molecular engineering, nanotechnology and synthetic biology, and in more applied fields such as translational medicine, food science, environmental science, climate studies, research on animals, sustainability, science education and others. The goal is to produce insights, tools and recommendations that are relevant not only for academic researchers and teachers, but also for civil society, policy makers and industry, as well as for professionals in education, health care and the media, thus contributing to better research practices, better policies, and a more sustainable global society. Established in 2005 as Genomics, Society and Policy, the journal has gradually expanded its area of research and critical reflection, particularly encouraging interdisciplinary collaboration and now developing along four main directions: How science and innovation affect society and the environment, and how responsible research can integrate societal needs and concerns in the process of research, with a strong focus on sustainability,  responsibility and public engagement Where humanities and science meet: multidisciplinary and interdisciplinary scholarship, for instance on neuro-enhancement and digitalisation How research can inform evidence-based practices and policies How philosophical traditions (such as phenomenology, hermeneutics, dialectics, psychoanalysis, pragmatism, and critical theory) can help to understand and address concrete issues of emerging life sciences and technologies. As all the topics in scope and disciplines are addressed from an international and global perspective, the journal welcomes submissions from all countries and regions around the world on a broad range of subjects, including quantitative or qualitative research and case studies. The editors also welcome suggestions for thematic series. Topics addressed through contributions within the journal might include, but will not be restricted to: Human bioethics Societal and cultural relevance of genomics Ethical, legal, and social implications/aspects of emerging sciences (ELSI/ELSA) Responsible research and innovation (RRI) Constructive and interactive technology assessment Sustainability, biodiversity and climate change Neuro-ethics and cognitive enhancement Artificial intelligence and automation Animal bioethics Mental health ethics and policy Sexuality and gender identity Organizational ethics Environmental bioethics Bioethics, world-views and religion Bioethics and gender Pediatric and family ethics Philosophy of medicine Rural and developmental bioethics Public health ethics Race and culture/ethnicity Reproduction The journal has an international multidisciplinary editorial board with leading academics in the fields of ethics, philosophy, bioethics, social sciences, genomics, political science, sociology and economics.